Methylation and loss of Imprinting: Unending rivalries unleashed between Ã¢â‚¬Å“kneaded erasersÃ¢â‚¬Â and Ã¢â‚¬Å“fate writersÃ¢â‚¬Â - Farooqi, Ammad Ahmad; Dilawar, Bilal Ahmed; Khanum, Reema; Chaudhary, Sumaira; Bhatti, Shahzad (Research in Biotechnology, 2010)
Genome is a complex barcode that is interpreted at molecular level. There are various proteins which are modulating the expression or repression of the genes. Miscellaneous proteins work in collaboration to stimulate or repress the gene expression. Chromatin remodeling factors are the artists which chisel, carve and mould the sculpture of genome. In this review we will emphasize on exemptions and extensions which trigger genomic instability in broad range of molecular anomalies. Doubtlessly therapeutic interventions have shown tremendous promise in cancer therapy, but the selectivity profiles of these compounds have largely relied on serendipity or 'off-target' activities rather than rational drug design. Purposefully designed compounds with activity against methyltransferase, demethylase and HDAC will bring us a step closer to personalized medicine.